PENGARUH MANAJEMEN LABA, AGRESIVITAS PAJAK, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Irsyad Syuhada (2023)
The research aims to obtain empirical evidence concerning the role of Earnings Management, Tax Aggressiveness, and Institutional Ownership related to the Disclosure of Corporate Social Responsibility or CSR. The research population is the mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2020. Purposive sampling is an approach used to determine the sample in this research, whereas the sample obtained is 36 mining companies. Data testing and analysis were carried out using the STATA application's Panel Data approach. The results of the study found that institutional ownership and earnings management did not affect the disclosure of corporate social responsibility. However, it was found that tax aggressiveness has a significant effect on the Disclosure of Corporate Social Responsibility. The limitations of this study are the small number of companies that can be observed and the assessment of corporate social responsibility disclosure which is subjective in nature, resulting in inconsistent results from one study to another.